Vida Alone and in Tank Mixtures for Kochia Control in Fallow - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2019)
To learn more about kochia control in fallow, a comparison of Vida alone and in tank mixtures was conducted. Glyphosate alone provided no more than 40% kochia control, and was similar to Vida or 2,4-D alone late in the season. The tank mixture of Vida plus Gramoxone and Spartan controlled kochia the best regardless of rating date, and was the only treatment to provide more than 95% control at 28 days.
Keywords: herbicide resistant weeds